Embedded Kinetic Simulation of Ganymede's Magnetosphere: Improvements and Inferences. Issue 7 (22nd July 2019) - Zhou, Hongyang; Tóth, Gábor; Jia, Xianzhe; Chen, Yuxi; Markidis, Stefano
Abstract: The largest moon in the solar system, Ganymede, is also the only moon known to possess a strong intrinsic magnetic field and a corresponding magnetosphere. Using the new version of Hall magnetohydrodynamic with embedded particle‐in‐cell model with a self‐consistently coupled resistive body representing the electrical properties of the moon's interior, improved inner boundary conditions, and the flexibility of coupling different grid geometries, we achieve better match of magnetic field with measurements for all six Galileo flybys. The G2 flyby comparisons of plasma bulk flow velocities with the Galileo Plasma Subsystem data support the oxygen ion assumption inside Ganymede's magnetosphere. Crescent shape, nongyrotropic, and nonisotropic ion distributions are identified from the coupled model. Furthermore, we have derived the energy fluxes associated with the upstream magnetopause reconnection of ∼10 −7 W/cm 2 based on our model results and found a maximum of 40% contribution to the total peak auroral emissions. Key Points: Hall MHD‐EPIC model of Ganymede's magnetosphere uses realistic inner boundary conditions and energy‐conserving PIC scheme Ion‐scale kinetics at upstream magnetopause are fully resolved, shown by the nongyrotropic/anisotropic distributions Electron precipitation of ∼10 −7 W/cm 2 shows up to half of the peak emission brightness contributed by upstream reconnection